Sugarcane thi1 homologues: a molecular and functional study - Vieira, Andréia Prata (2018)
Thiazole biosynthetic protein (THI1) is involved in the synthesis of the thiazole ring, a thiamine (vitamin B1) component. Thiamine is an essential co-factor in several carbohydrate and amino acid metabolic pathways. Prokaryotes and a few eukaryotes, such as fungi and plants, are able to synthesize thiamine de novo. These organisms contain the genes that encode the corresponding enzymes (such as THI1) that perform this metabolic function. THI1 actually functions as a reagent rather than as a conventional catalytic enzyme, as the THI1 polypeptide itself serves as the sulfide donor for thiazole formation. This gene also plays a role in organelle DNA damage tolerance. Arabidopsis thaliana has only one copy of the thi1 gene (At-thi1). Transcripts derived from At-thi1 are targeted simultaneously to chloroplasts and mitochondria by differential usage of two in-frame initiation codons. The tz-201 A. thaliana thi1 mutant has been shown to accumulate more sucrose in its tissues than wild-type plants. This suggests that a better understanding of thi1 genes and the role they play in cellular sucrose accumulation may be relevant for improving commercially important crops such as sugarcane. Sugarcane (Saccharum spp.) is a C4 photosynthesis monocot. Unlike A. thaliana, sugarcane has at least two thi1 copies (sc-thi1.1 and sc-thi1.2), as do the other C4 grasses. This thesis concerns the molecular and functional analyses of sugarcane thi1 (sc-thi1) gene homologues. The identified alleles related to sc-thi1.2 have some differences in sequence and seems to be diverging into two subgroups (sc-thi1.2a and sc-thi1.2b), based on phylogenetic analyses. Expression analysis showed that each sc-thi1 copy is expressed differentially in individual tissues and in developing stages levels. Subcellular analysis showed that sc-thi1.1 and sc-thi1.2b have the same cellular distribution pattern, distinct from the observed for sc-thi1.2a. Sc-thi1.1 and sc-thi1.2b were also able to partially complement thiamine auxotrophy in a yeast mutant deficient in thiamine biosynthesis. A similar complementation assay is not possible in the A. thaliana tz-201 mutant owing to low transformation efficiencies. Thus, Physcomitrella patens was chosen to generate thi1 mutant lines for future functional complementation studies. P. patens is a moss used as a plant model, with a small size, short life cycle and a haploid dominant phase. Despite its simplicity, it has six thi1 homologues copies. Homologous Recombination was used to generate P. patens thi1 mutants. In each case, a target thi1 gene was disrupted by replacing its coding region with an antibiotic resistance gene cassette. Single mutants were obtained for all six thi1 gene copies. All the knockout lines were able to survive and grow with only minor effects on morphology and physiology. Deletion of one of the thi1 gene copies (PpThi1.20F) drastically affected protoplast survival and regeneration, suggesting a role for this gene in early (polar) cell division and differentiation. The experimental design, which permits recycling of the selectable marker cassettes, provides a research platform for the construction of double, triple, quadruple or quintuple mutants in the future. The individual mutants line generated in this work, as well as the possible multiple mutants, will be useful for thi1 functional complementation experiments and for discerning the specific functions of individual thi1 gene family members.